(untitled) (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2026)
Soybeans are a secondary crop that plays a crucial role in the national food supply due to their high nutritional value. The insect pest Callosobruchus analis (Coleoptera: Bruchidae) frequently attacks black soybeans during storage, reducing their weight by up to 98%. One way to prevent damage to black soybean seeds is to use a botanical insecticide, namely bintaro leaf powder. Research aims to determine and study the effect of different doses of bintaro leaf powder on the development of insect pests C. analis and the quality of black soybean seeds of Detam-1 variety. This research was conducted at the Laboratory of the Faculty of Agriculture, Winaya Mukti University, Tanjungsari Sumedang. This research began in April to June 2024. The experimental design used was a Completely Randomized Design with 6 treatments and 4 replications consisting of A = 0, 00 g of bintaro leaf powder /100 g of black soybean seeds, B = 3.00 g of bintaro leaf powder/100 g of black soybean seeds, C = 6.00 g of bintaro leaf powder/100 g of black soybean seeds, D = 9.00 g of bintaro leaf powder/100 g of black soybean seeds, E = 12.00 g of bintaro leaf powder/100 g of black soybean seeds, F = 15.00 g of bintaro leaf powder/100 g of black soybean seeds. The results showed that different doses of bintaro leaf powder gave a real effect on mortality, number of eggs, number of larvae, number of pupae and number of imago. Treatment of bintaro leaf powder F = 15.00 g bintaro leaf powder showed the best results.